KESAMAAN KOMUNITAS BURUNG DI LEMBAH PALU SULAWESI TENGAH - Ihsan, Moh (Universitas Tadulako, 2015)
This study was conducted at three locations in the Palu Valley conservation area, namely in Paneki, Wera and Ngatabaru.Â Research on the types of birds at each study site by using a modification of the method IPA (Indices Ponctuel d'Abondance).Â All sites have found as many as 59 species of birds with a total population of 849 were included in 33 families. Grey-rumped treeswift bird is a bird species dominant at all the study sites.Â Overall the types of birds from one location to study the similarity rate is low (<50%). Location of the greatest degree of similarity are Wera and Ngatabaru by 49%, then Wera and Paneki of 47% and location Paneki and Ngatabaru by 43%.Keywords: Similarity communities, birds, Palu valley